Design and Synthesis of Multipurpose Derivatives for N‐Hydroxyimide and NHPI‐based Catalysis Applications. Issue 45 (3rd December 2021) - Caruso, Manfredi; Petroselli, Manuel; Cametti, Massimo
Abstract: Bi‐ and tricyclic derivatives 1 a and 2 a (Scheme 2) combining the catalytic N‐hydroxyimide NO−H unit with the imidazole moiety were designed as multipurpose derivatives and proposed as chemical tools for achieving improved homogeneous and heterogeneous aerobic oxidation catalysis. BDE tunability, formation of a ZIF and of imidazolium ionic‐liquid‐like materials were obtained for N‐hydroxyphthalimide (NHPI)‐based 2 a and here described. Abstract : Novel design for N‐Hydroxyimide and NHPI‐based derivatives has been presented here with the aim of providing multipurpose derivatives for homogeneous and heterogeneous radical catalysis applications in aerobic oxidation reactions. Tunable bond dissociation energy, the capability to form ZIF materials and be able give access to ionic liquid‐like species have been demonstrated for 2 a, paving the way to future development in the field.